The fate of pulmonary conduits after the Ross procedure: longitudinal analysis of the German-Dutch Ross registry experience. Issue 24 (23rd October 2013) - Mokhles, M Mostafa; Charitos, Efstratios I; Stierle, Ulrich; Rajeswaran, Jeevanantham; Blackstone, Eugene H; Bogers, Ad J J C; Takkenberg, Johanna J M; Sievers, Hans-Hinrich
Abstract : Objective: To assess allograft function over time after the Ross procedure. Design: Prospective multicentre registry. Setting: 10 cardiac surgery departments in Germany and the Netherlands. Patients: Among 1775 consecutive adult patients (mean age 43.7±12.0) who underwent the Ross procedure, 1645 (93%) received an allograft (pulmonary=1612, aortic=12, unknown=21), 120 (6%) a bioprosthesis, and 5 (0.3%) a bovine jugular vein for right ventricular outflow tract reconstruction. Intervention: Ross procedure. Main outcome measures: Using non-linear longitudinal models, serial echocardiographic records (N=6950) were studied to assess pulmonary conduit function over time in patients who had undergone the Ross procedure, with a maximum echocardiographic follow-up of 22.4 years (5.5±4.3 years). Results: A slight increase in pulmonary conduit regurgitation grade was observed during follow-up. Freedom from regurgitation grade ≥2+ was 95% after 14 years. Female patient gender, allograft use (compared to bioprosthesis), male donor gender, antibiotic treatment of the allograft, and specific surgical adjustments were associated with a significantly higher regurgitation grade. Mean conduit gradient increased from 4.7 mm Hg at 1 month to 10 mm Hg by 14 years, while peak gradient increased from 8.4 to 18.5 mm Hg. Smaller conduit diameter, male patient gender, younger patient age, younger donor age, and use of a bioprosthesis were associated with a significantly higher mean and peak gradient. During follow-up, 76 reinterventions were required on the pulmonary conduit in 67 patients. Freedom from pulmonary conduit reintervention or dysfunction was 90.6% (95% CI 87.7% to 93.6%) and 79.5% (95% CI 75.2% to 84.0%) at 15 years, respectively. Conclusions: Echocardiographic follow-up of pulmonary conduits shows good conduit durability. Clinically important conduit regurgitation and stenosis are rare in adult patients after the Ross operation.